2023
DOI: 10.3390/foods12162982
|View full text |Cite
|
Sign up to set email alerts
|

The Application of Biometric Approaches in Agri-Food Marketing: A Systematic Literature Review

Lei Cong,
Siqiao Luan,
Erin Young
et al.

Abstract: A challenge in social marketing studies is the cognitive biases in consumers’ conscious and self-reported responses. To help address this concern, biometric techniques have been developed to obtain data from consumers’ implicit and non-verbal responses. A systematic literature review was conducted to explore biometric applications’ role in agri-food marketing to provide an integrated overview of this topic. A total of 55 original research articles and four review articles were identified, classified, and revie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 99 publications
0
6
0
Order By: Relevance
“…Despite these fluctuations, the linear trend in publication numbers shows a steady increase. Accordingly, studies using eye tracking as an instrument in the research field are experiencing growing research interest, which is also confirmed by other reviews [2,16,18].…”
Section: Annual Publications and Publication Trendmentioning
confidence: 53%
See 4 more Smart Citations
“…Despite these fluctuations, the linear trend in publication numbers shows a steady increase. Accordingly, studies using eye tracking as an instrument in the research field are experiencing growing research interest, which is also confirmed by other reviews [2,16,18].…”
Section: Annual Publications and Publication Trendmentioning
confidence: 53%
“…It can be considered a starting point for eye tracking research as Bialkova and van Tjip [38] (p. 592) stated that eye tracking "seems to be a promising tool for answering puzzling questions in consumer attention and decision-making with straightforward potential extensions to enlarge its scope." This is also supported by the increase in the number of publications in the following years (see Figure 2), which shows that eye tracking as an instrument of investigation became increasingly important in consumer research [2,16,18].…”
Section: Key Findings and Future Research Directionsmentioning
confidence: 59%
See 3 more Smart Citations